Paralog-Dependent Specialization of Paf1C Subunit, Ctr9, for Sex Chromosome Gene Regulation and Male Germline Differentiation in Drosophila. - Kai, T.; Zheng, J.; Iki, T. (Genes to cells : devoted to molecular & cellular mechanisms, 2025)
Testis-specific gene regulatory mechanisms govern the differentiation of germ cells into mature sperm. However, the molecular underpinnings are not fully elucidated. Here, we show the subunits forming Paf1C, a transcription regulator complex conserved across eukaryotes, have their individual paralogs predominantly expressed in Drosophila testes. One of these, namely, Ctr9 paralog enriched in testes (Ctr9t) was found to play a critical and nonredundant role in postmeiotic spermatid differentiation and male fertility in D. melanogaster. A proximity proteome analysis provides evidence that Ctr9t prefers the interaction between paralog members. We show endogenous Ctr9t is expressed and functional in germ cells at spermatocyte stages, accumulating in a distinct compartment within the nucleolus. There, Ctr9t co-localizes with Spermatocyte arrest (Sa), a testis-specific paralog of TATA-binding protein (TBP)-associated factor 8 (TAF8). We further demonstrate that ctr9t function is crucial for maintaining Sa in the nucleolus, but not vice versa. Transcriptome profiling reveals that Ctr9t acts as an activator for the set of male fertility genes on the Y chromosome, but it also acts as a global repressor of X chromosome genes. Collectively, our results shed light on the nucleolus-associated, paralog-dependent regulation of gene expression from sex chromosomes, which ensures the terminal differentiation of male germ cells.